Application of da Vinci surgery in hepatectomy - Shiliu Lu; Guandou Yuan; Biao Lei; Bin Chen; Bangyu Lu; Shuiping Yu; Songqing He (Intelligent Surgery, 2022)
The first laparoscopic hepatectomy was performed over 30 years ago, and its safety and short-term and long-term outcomes are comparable to those of traditional laparotomy. Minimally invasive surgery is important for liver surgery. However, due to the limitations of its instruments and technology, laparoscopic surgery still has certain challenges in the field of liver resection, which is also an important reason for the relatively slow implementation of laparoscopic liver resection. The advent of the da Vinci robotic surgical system has helped to overcome the shortcomings of laparoscopy, such as the difficulty in exposing some special liver segments and performing sutures and reconstruction. Based on the experience of the authors’ surgical team, this paper explores the application value and breakthrough of the da Vinci robot in minimally invasive hepatectomy from the aspects of perioperative evaluation, lesion localization, bleeding control, surgical approaches, and precautions for complications.